Peran Perempuan dalam Meningkatkan Kesejahteraan Ekonomi Keluarga di Desa Maneron, Kabupaten Bangkalan - Zahro, Zamrotus; Ruski; Ulum, Romiftahul (Jurnal Pendidikan Ekonomi Undiksha, 2022)
The role of women in general is to manage matters related to the household, serve the needs of their husbands and take care of children, but with the development of the times, many women decide to work, compared to the situation of women in the eighties where they just stayed at home taking care of the house. stairs, women are considered not to be able to work as well as men. Working women is a common thing in today's modern era, with this women can develop their potential. The purpose of this research is to find out how the role of housewives in Maneron Village, Sepulu District, in improving the economic welfare of the family. The results of this study show that the role of housewives in the family in Maneron Village is not only based on the assumption that women only end up in the kitchen and take care of the family but also have a role in helping and improving the family's economic standard.